A Case Report Capecitabine-Induce Grade II Hand and Foot Syndrome - Nurul Damayanti; Putri Ramadhani; Khusnul Fitri Hamidah; Husin Thamrin (Keluwih)
Abstract—Capecitabine has a common side effect of hand and foot syndrome (HFS). It is cutaneous capecitabine’s adverse effect, which generally occurs within 11 to 360 days. In this case report assesses the delayed onset of capecitabine because HFS did not occur within 11-360 days but rather took longer, specifically 720 days. A female patient of 82 years old with a history of breast cancer was diagnosed four years ago. She did not undergo radiation and surgery, only capecitabine tablets as neoadjuvant therapy since April 2021. In August 2023, the patient complained of pain, dryness, and blood in both legs. Analysis of side effects of the drug was carried out using the Naranjo Probability Scale. Therapy management during hospitalization involves stopping capecitabine and performing wound care by applying fusidic acid cream and the patient's complaints improved on the eleventh  day of therapy. Capecitabine discontinuation is the most effective strategy to minimize the effect of HFS. Further research is to determine the effectiveness of emollient application as a prevention for HFS.